Pengalaman Psikologis Pasien Covid-19: Literatur Review - Wenny Nugrahati Carsita; Alvian Pristy Windiramadhan (Universitas Harapan Bangsa Purwokerto, 2021)
The Covid-19 disease causes global health problems. The increasing number of cases and deaths causes infected patients to experience not only physical suffering but also psychological problems. Patients infected with Covid-19 report anxiety, depression and post-traumatic stress. Patients with psychological problems will have difficulty controlling the symptoms of the disease, which will prevent recovery. This study aims to determine the psychological experience of Covid-19 patients. The research method used literature review. The data search was sourced from Google scholar, Pubmed, Science direct, and ProQuest using the keyword